Identifikasi Kebutuhan Psikologis Remaja dengan Gangguan Depresi di Surabaya - Author: Hamidah; Marlina S. Mahajudin (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
The purpose of this study was to get information about the psychological needs of adolescents with depressive disorders. The information was revealed: 1. the number and levels of depression, 2. Psychological needs, 3. support needs, 4. Close people needed. The method used was survey, with a descriptive analysis. Subjects were 1054 people, which consist of 570 men and 484 women in 2nd grade of State and Private Senior High School in Surabaya. Results of the study that there was 0% teens that don't have depression and depression in mild, 42 people (4.022%) were depressed, 917 people (87.8%) had major depression, 95 people (9.09%) had acute depression. Acute depression disorders experienced more in female subjects than in males, that is 11, 98% to 6.49%. Forms of psychological needs of adolescents with depression is social support such as: information related to depression as much as 10.7%, emotional support (encouragement, affection, closeness and willingness to listen complaints) 40.8%, financial support (provide facilities to entertain themselves, switch to eat and go to a place of entertainment, refreshment or a walk and exercise) 16.7%, moral support (advice, discourse, confidence and calmness) as much as 31.8%. Initial action was to lock themselves alone and do reflection as much as 38.6%; entertaining themselves as much as 15.4%; having exercise as much as 10.9%; having refreshment 35.1%. Actions to solve issue are sharing with friend as much as 48.7%; sharing with parents as much as 15.4%; silent as much as 30.8% and others as much as 5.1%. The expected parenting type is democratic 95%, authoritarian as much as 1% and the remaining 4% is permissive.Key words: adolescents, depression and psychological needs